2006
DOI: 10.1007/s11934-006-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel kinase inhibitors in renal cell carcinoma: Progressive development of static agents

Abstract: The rapidly expanding knowledge regarding neoplastic diseases is providing a plethora of new targets for drug discovery and development as exemplified by recent data in renal cell carcinoma. The initial experience with molecularly "targeted" agents has demonstrated that development of the newer non-cytotoxic agents will provide unique challenges requiring modification of many traditional drug development concepts and methods. We discuss recently reported data from a few renal cell carcinoma trials with putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Although senescence is an established form of clonogenic cell death in response to many treatments, including IR, it is possible that some cells interpreted in this study as being senescent may still have been viable and, yet, were not actively contributing to cfDNA release. Many cancer treatments may primarily exert a cytostatic effect, promoting growth arrest without subsequent cfDNA release into circulation (Desai and Stadler, 2006;Martin and Schilder, 2006;Winquist et al, 2006;Ewald et al, 2010). These complexities highlight the need to better understand the relationship between the mechanism of action of a particular treatment and biological responses observed within distinct cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Although senescence is an established form of clonogenic cell death in response to many treatments, including IR, it is possible that some cells interpreted in this study as being senescent may still have been viable and, yet, were not actively contributing to cfDNA release. Many cancer treatments may primarily exert a cytostatic effect, promoting growth arrest without subsequent cfDNA release into circulation (Desai and Stadler, 2006;Martin and Schilder, 2006;Winquist et al, 2006;Ewald et al, 2010). These complexities highlight the need to better understand the relationship between the mechanism of action of a particular treatment and biological responses observed within distinct cell types.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] An emerging strategy to overcome this therapy resistance is with cytostatic agents that disable the proliferation and growth of the tumor cells and synergize in combination with cytotoxic drugs. [29][30][31] Cellular senescence is a form of persistent cytostatic response by the cells to the stress, wherein cells undergoing senescence cease to proliferate but can remain metabolically active and viable. 32 Therapyinduced senescence is considered an important route to achieving therapeutic sensitivity for tumor cells that are resistant to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a clinically relevant increase in CR and OS has not been reported and the role of TT in increasing the curability of mRCC has not been fully elucidated. From a pharmacological viewpoint, the unsatisfactory results of TT to induce a CR may be explained in part by their mechanism of action, which appears to be more cytostatic than cytotoxic [ 15 ]. The current study also showed that the OS (15.8 months), ORR (33.9%), and CR (5.6%) of TT were either similar or inferior to the OS (16.5 months), ORR (31.1%), and CR (10.4%) of IT ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%